Respuesta :
Answer:
−x^2+7x−5
Step-by-step explanation:
---- times this by 1 (3x^2+4x−3) −(4x^2-3x+2) ---- times this by - 1
3x^2+4x−3−4x^2+3x−2
3x^2+4x−3−4x^2+3x−2 - collect like terms
(3x^2+−4x^2)+(4x+3x)+(−3+−2) - solve it
(3x^2+−4x^2)= −x^2
(4x+3x) = 7x
(−3+−2) = −5
−x^2 + 7x−5
Answer:
−x^2+7x−5
Step-by-step explanation:
times this by 1 (3x^2+4x−3) −(4x^2-3x+2) ---- times this by - 1
3x^2+4x−3−4x^2+3x−2
3x^2+4x−3−4x^2+3x−2 - collect like terms
(3x^2+−4x^2)+(4x+3x)+(−3+−2) - solve it
(3x^2+−4x^2)= −x^2
(4x+3x) = 7x
(−3+−2) = −5
−x^2 + 7x−5